Differential Expression of Sumoylation Enzymes SAE1, U BA2, UBC9, PIAS1 and RanBP2 in Major Ocular Tissues of Mouse Eye - Nie, Qian; Yang, Lan; Qing, Wenjie; Xie, Jie; Gong, Xiaodong; Chen, Huimin; Gan, Yuwen; Wang, Ling; Xiang, Jia-Wen; Xiao, Yuan; Chen, Zhigang; Li, David Wan-Cheng (Current Molecular Medicine, 2018)
It is now well established that protein sumoylation is an important mechanism to regulate multiple cellular processes including gene transcription, chromatin structure, cell proliferation and differentiation, as well as pathogenesis. In the vertebrate eye, we and others have previously shown that sumoylation can regulate differentiation of major ocular tissues including retina and lens. However, the expression patterns of the three types of sumoylation enzymes, the activating enzymes SAE1 and UBA2, the conjugating enzyme UBC9, and the ligating enzymes such as RanBP2 and PIAS1 have not been well studied in the ocular tissues. In the present study, using QRT-PCR and western blot analysis, we have determined the differentiatial expression patterns of the above three types of enzymes, and the obtained results lay down a foundation for further exploration of sumoylation functions in vertebrate eye.
Keywords: sumoylation enzymes